Penyuluhan Tentang Menstruasi Pada Remaja Putri Di SMP Negeri Kabupaten Enrekang - Nurhaedah, Nurhaedah; Pannyiwi, Rahmat; Rosdiana, Rosdiana; Latif, Sarifudin Andi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Menstruation is increasingly recognized as an issue in domestic and global public health. In addition, matters related to menstruation are still considered taboo and have a negative stigma and it is often difficult to practice optimal menstrual hygiene for adolescents and adults in various countries and regions. Many girls do not have a proper understanding that menstruation is a normal biological process. They actually only know about it at menarche, aka when they first experience menstruation. This community service activity was carried out in the Enrekang Regency State Middle School Hall with a total of 41 Young Women on October 27 2022 using the counseling method in the form of lectures. From this Community Service Activity, it was concluded that the implementation of menstruation education for young women in the Enrekang Regency State Middle School Hall went well, as many as 41 people participated in this activity with enthusiasm as seen from the responses of children who paid good attention and also asked questions during the Q&A session.